Persepsi remaja terhadap perilaku emotional eating - Nindya Alifia Tittandi (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2022)
Adolescence is a transitional period which is usually marked by significant emotional changes. Some teenagers still have difficulty coping with the emotions they are experiencing, so they choose to calm them down by eating. This can be known as emotional eating. However, many adolescents do not know and realize this behavior, which if done excessively can lead to overweight or even obesity. So through this research, we try to find out the extent of adolescent knowledge regarding emotional eating behavior. Our findings indicate that differences in school levels determine this knowledge, so that the provision of material related to eating disorders is not fully understood by adolescents. In fact, the prevention of obesity in adolescents is more effective if given since early adolescence, namely by including the curriculum in schools related to self-control and basic knowledge related to eating disorders and other disorders that generally begin to occur in adolescence.